PHATIC COMMUNICATION RESEARCH IN THE ANTHROPOCENTRIC PARADIGM (American Journal of Research in Humanities and Social Sciences, 2024)
In modern anthropocentric linguistics, there is a growing interest in the scientific substantiation of similarities and differences in the forms of interpersonal communication. These similarities and differences are associated with such factors as value orientations, norms of communicative behavior appropriate to the situation, a person’s belonging to a certain social and/or ethno-cultural group, as well as the influence of personal motives on the choice of strategic models of communication. This is because linguists no longer separate language from man, do not see language as an independent entity, and confirm W. Humboldt’s idea that man cannot be studied without language, and language without man.